IDENTIFIKASI PENGARUH PERUBAHAN FUNGSI LAHAN TERHADAP SOSIAL EKONOMI MASYARAKAT DI PINGGIRAN KOTA (Studi kasus: Kecamatan Palu Utara) - Lutfi, Lutfi (MEKTEK, 2006)
The general aim of the studi was to identify the influence of spatial and social transformation process tha had been taking place (2003) on the social prosperity of the urban fringe community. The particular aims of the study were (1) to identify the changing effects of the land function as the result of the new settlement development toward the social economic contidion of community in the urban fringe, and (2) to identify the social interaction pattern of local community.The result of the study indicated that were changing effects of the land function from cultivation land toward non-cultivation land (the harbor development) on the range of family income of the local community (social economic condition).It could be concluded that with regard to the physical change of the land, most of people who had previosly had a job in the cultivation sector moved to another job (informal sector); while the rest had never had a job. Furthermore, seen from the social economic point of view it was discovered that the research areas were expanded areas of city dwellers with their urban characteristics. factors